Comparative effectiveness of biologics in clinical practice: week 12 primary outcomes from an international observational psoriasis study of health outcomes (PSoHO). (29th July 2022) - Pinter, Andreas; Puig, Luis; Schäkel, Knut; Reich, Adam; Zaheri, Shirin; Costanzo, Antonio; Tsai, Tsen Fang; Smith, Saxon D.; Lynde, Charles; Brnabic, Alan; Reed, Catherine; Hill, Julie; et al.
Abstract: Background: Clinical trials study treatment outcomes under stringent conditions, capturing incompletely the heterogeneity of patient populations and treatment complexities encountered in real‐world practice. Objectives: To compare the effectiveness of anti‐interleukin (IL)‐17A biologics relative to other approved biologics in patients with moderate‐to‐severe psoriasis. Methods: The Psoriasis Study of Health Outcomes (PSoHO) is an ongoing 3‐year observational cohort study in adults with chronic moderate‐to‐severe plaque psoriasis initiating or switching to a new biologic. Primary study endpoint is the proportion of patients achieving 90% improvement in Psoriasis Area and Severity Index (PASI 90) and/or static Physician Global Assessment (sPGA) 0/1 at Week 12 (W12) in the anti‐IL‐17A cohort (ixekizumab [IXE], secukinumab) vs. all other approved biologics. Secondary outcomes include the proportion of patients who achieve PASI 75/90/100, absolute PASI scores ≤5, ≤2 and ≤1, Dermatology Life Quality Index (DLQI) score of 0/1 at W12 between the two cohorts and among the individual biologics. Comparative effectiveness analyses were conducted using Frequentist Model Averaging (FMA), a novel causal inference machine learning approach. Missing data for binary outcomes were imputed as non‐response. Results: Patient profiles in the anti‐IL‐17A cohort and other biologics cohort were similar, with more frequent comorbid psoriatic arthritis and less frequent exposure to conventional treatments in the patients receiving anti‐IL‐17A biologics. At W12, 71.4% of patients who received an anti‐IL‐17A biologic achieved PASI 90 and/or sPGA 0/1 compared to 58.6% of patients who received other biologics (odds ratios [OR], 1.9; 95% confidence intervals [CI], [1.6, 2.4]). Similar findings were observed for secondary outcomes. Conclusions: These results reflect the high efficacy and early onset of skin clearance of IL‐17A inhibitors observed in randomized clinical trials and confirm the effectiveness of anti‐IL‐17A biologics in the real‐world setting.